Hydrothermal Synthesis of Bi2S3 Nanorods from a Single-Source Precursor and Their Promotional Effect on the Photocatalysis of TiO2. (21st May 2013) - Lu, Juan; Wang, Zuoshan; Zhang, Ying; Zhou, Xiufeng
Abstract : As a direct bandgap semiconductor, Bi2 S3 has the potential ability to improve the photocatalytic activity of nano-TiO2 due to its low energy gap (E g = 1 . 3  eV). In this study, large-scale uniform Bi2 S3 nanorods were synthesized by a hydrothermal treatment, using Bi[S2 P(OC4 H9 )2 ]3 as the single-source precursor. Characterization results show that as-prepared samples belong to an orthorhombic phase of Bi2 S3, and the products mainly crystallize in the form of nanorods which measure ca. 200 nm in length and ca. 50 nm in diameter. The photo-catalytic experiments for the degradation of methyl orange under visible irradiation revealed that a small amount of as-prepared Bi2 S3 in our study would significantly improve the photo-catalytic activity of nano-TiO2, whether Bi2 S3 is introduced by a physical way or a chemical way. However, excess Bi2 S3 will lead to a decrease in the catalytic efficiency of TiO2 when Bi2 S3 was introduced by a chemical way; it never happened when Bi2 S3 was introduced by a physical way. Even so, among all as-prepared samples, the TiO2 -based photo-catalyst with 3 wt.% Bi2 S3 introduced by a chemical way exhibits the best catalytic performance under visible irradiation.